Matrix metalloproteinase-9 is elevated and related to interleukin-17 and psychological stress in male infertility: A cross-sectional study - Ann Prasad Mary; Hanumanthappa Nandeesha; Dasari Papa; Thyagaraju Chitra; Rajesh Nachiappa Ganesh; Vikas Menon (Shahid Sadoughi University of Medical Sciences, 2021)
Background: Matrix metalloproteinase-9 (MMP-9), interleukin-17 (IL-17) and psychological stress are known to play a role in the pathogenesis of male infertility. Objective: To assess the association of MMP-9 with IL-17 and psychological stress in infertile men. Materials and Methods: In this cross-sectional study, 39 men with infertility diagnosed based on semen analysis and 39 subjects with normal semen analysis were included in the study. MMP-9 and IL-17 were estimated in both groups by ELISA. Perceived stress scale was used to assess psychological stress in controls and cases. Results: In infertile cases, MMP-9 and IL-17 were significantly increased when compared with controls (p = 0.046, p = 0.041 respectively). A significant association of MMP-9 was observed with IL-17 (r = 0.335, p = 0.037) and perceived stress scale (r = 0.329, p = 0.041). Conclusion: IL-17 and stress increase MMP- 9 levels in infertile men.